Study of Optimized Coupling Based on Micro-lensed Fibers for Fibers and Photonic Integrated Circuits in the Framework of Telecommunications and Sensing Applications - Le, Si Dat; Delcourt, Enguerran; Girault, Pauline; Gutierrez-Arroyo, Aldo; Azuelos, Paul; Lorrain, Nathalie; Bodiou, Loïc; Poffo, Luiz; Goujon, Jean-Marc; Dumeige, Yannick; Hardy, Isabelle; Rochard, Philippe; et al. (Communications in Physics, 2017)
We demonstrate the interest of expanded beam microlenses (around 55 µm of mode field diameter) to relax positioning tolerances and to decrease reflectance in single mode fiber to fiber interconnexions.  We also point out the interest of micro-lenses of very small mode field diameter (around 2 µm) to improve coupling efficiency in specialty fibers and integrated waveguides for non linear effects based functions and for sensors applications at a wavelength of 1.55 µm.